A pathway for citizen science data to inform policy: A case study using eBird data for defining low‐risk collision areas for wind energy development. Issue 6 (13th April 2021) - Ruiz‐Gutierrez, Viviana; Bjerre, Emily R.; Otto, Mark C.; Zimmerman, Guthrie S.; Millsap, Brian A.; Fink, Daniel; Stuber, Erica F.; Strimas‐Mackey, Matthew; Robinson, Orin J.
Abstract: The research and conservation community has successfully harnessed the wealth of ecological knowledge found in unprecedented volumes of citizen science (CS) data world‐wide. However, few examples exist of the use of CS data to directly inform policy. Current examples of applications of CS data mainly stem from programs that are restricted in scope (e.g. defined protocols, restricted sampling time frame), and the potential use of unrestricted CS data to inform policy remains largely untapped. Here, we make a call for moving beyond questioning the reliability of CS data and present a case study of how the US Fish and Wildlife Service (USFWS) used information from an unrestricted CS program (eBird) to inform levels of exposure to collision risk for wind energy development. Policy implications . The USFWS made the technical recommendation to use eBird abundance estimates for the bald eagle as the only source of information to define low‐risk collision areas as part of the agency's wind energy permitting process. Our study contributes a clear pathway of how to realize the potential of unrestricted CS programs for generating the evidence base needed to inform policy decisions. Abstract : The USFWS made the technical recommendation to use eBird abundance estimates for the bald eagle as the only source of information to define low‐risk collision areas as part of the agency's wind energy permitting process. Our study contributes a clear pathway of how to realize the potential of unrestricted CS programs for generating the evidence base needed to inform policy decisions. Resumen: Las comunidades de investigación y conservación han logrado, de forma muy exitosa, aprovechar la gran cantidad de datos generada por la Ciencia Ciudadana, y disponibles a nivel mundial. Sin embargo, son pocos los casos en los cuales estos datos han servido para diseñar políticas. Los casos actuales provienen de programas de CC restringidos en su alcance (por ejemplo, protocolos definidos, muestreos de tiempo limitado); pero todavía no se ha llevado a cabo el uso de datos provenientes de programas de CC irrestringidos y con potencial para nutrir políticas. Hacemos un llamado para superar la etapa que cuestiona los datos de CC. Para tal efecto presentamos un estudio de caso en el cual el Servicio de Pesca y Vida Silvestre de EE.UU (U.S. Fish and Wildlife Service) utilizó los datos provenientes de un programa de CC irrestringido (eBird) para diseñar políticas de desarrollo eólico concerniente a los niveles de riesgo de colisión de aves. Implicaciones para las políticas . el Servicio de Pesca y Vida Silvestre de los EE.UU. emitió la recomendación técnica de utilizar los valores estimados de abundancia relativa para el águila calva. Dichos valores provienen de eBird, tomado como fuente única de información para definir áreas de bajo riesgo de colisión, como parte del proceso para adquirir permisos para el desarrollo eólico. Nuestro estudio aporta un esquema muy claro de cómo aprovechar el potencial de los datos ofrecidos por los programas irrestringidos de CC. para generar la evidencia necesaria para el diseño de las políticas.